Clinical law: what do clinicians want to know? The demography of clinical law - Wheeler, Robert (Journal of medical ethics, 2023)
This is the first description of the questions that clinicians ask a department of clinical law, relating to the legal rules applicable to the care of their patients. Objectives To describe in detail the demography of clinical legal enquiries made by clinicians of all professions concerning the care of their patients. To collate and categorise the varieties of enquiry, to identify phenotypic patterns. To provide colleges, regulators, commissioners, educators and the NHS with an insight into hitherto undescribed subject matter, better to understand and respond to this aspect of clinical practice. Design Prospective collection of all clinical legal referrals recorded in writing over 12 years by a department of clinical law. Setting An English Tertiary Hospital NHS Trust. Participants Clinical staff of the regulated professions, all seeking to have their clinical legal enquiries answered. Main outcome measures The description of the demography of clinical law. Results 1251 written records were identified and reviewed. These were divided into nine broad clinical legal subject areas (domains): mental disorders, parents and children, incapacity, consent for treatment, disclosure of private information, other statutory, regulated practice, professional practice, clinical practice. Within these, 149 clinical legal phenotypes were identified to which each case could be assigned. Conclusions Among a broad range of enquiries, recognisable clinical legal phenotypes exist and have for the first time been described and categorised. These are clinical situations which clinicians need to be able to recognise and equipped to deal with. Doing so will likely facilitate timely and better treatment.